Legal Protection For Creditors Holding Mortgage Rights On Double Certified Owned Land - Ningrum, Intan Permata; Lukman, Arsin (Jurnal Hukum dan Kenotariatan, 2023)
This article analyzes how legal protection is for creditors holding mortgage rights on land with multiple certificates. This article was prepared using doctrinal research methods with literature study using secondary data and analyzed juridically-qualitatively by examining applicable regulations. The Mortgage Law gives the right of droit de preference or priority to creditors holding mortgage rights. However, in practice, this right is often injured by disputes over collateral rights, one of which is the dispute over the issuance of multiple certificates. In these conditions, the Land Office as the agency that issues the certificate has legal responsibility for the emergence of two certificates for land which of course is very detrimental to creditors. This is regulated in Article 54 paragraphs (1) and (2) of the Regulation of the Head of BPN RI Number 3 of 2011 concerning Management, Assessment and Handling of Land Cases. The Land Office has the obligation to cancel one of the duplicate certificates and announce it to the public. Thus, this action was taken to ensure order and certainty in land matters and maintain the integrity and public trust in the land system, as well as protect the legal position of creditors holding mortgage rights to land.